Malaysian legal provisions and design risks in construction works/ Zul Zakiyuddin Ahmad Rashid - Ahmad Rashid, Zul Zakiyuddin (Institute of Graduate Studies, UiTM, 2012)
Construction project is shrouded with various aspects of risks, which includes risks related to design professionals and design works. In order to complete a construction project successfully, the parties involved must be able to manage the risks. Although the need and importance of risk management cannot be denied, the standard of risk management among the parties involved in a construction project in Malaysia differs from one company to another. This is due to various factors such as the company resources for risk management, types and size of the project. As such there is a need to standardize the basic practice of risk management among the parties involved, to secure the safety and proper performance of the project. This can be achieved through legal measures, where certain requirement on risk management can be imposed to ensure the least required practice of risk management is exercised. This research is meant to look at the risks associated with design professionals and design works under the traditional procurement route in Malaysia and the role of Malaysian law in corresponding to the practice of standard risk management by the parties involved.